Effects of short-term spinal cord stimulation on patients with prolonged disorder of consciousness: A pilot study - Zhuang, Yutong; Yang, Yi; Xu, Long; Chen, Xueling; Geng, Xiaoli; Zhao, Jizong; He, Jianghong (Frontiers in Neurology, 2022)
Background Spinal cord stimulation (SCS) can improve the level of awareness of prolonged disorder of consciousness (pDOC), but its application is restricted due to damage of invasive operation. Short-term spinal cord stimulation (st-SCS) in a minimally invasive manner will better balance the benefits and risks. Objectives This study focuses on the safety and efficacy of st-SCS for pDOC and reveals the modulation characteristics of different frequencies of SCS. Methods 31 patients received 2-week st-SCS treatment and 3-months follow-up. All patients were divided into two types of frequency treatment groups of 5 Hz and 70 Hz according to the postoperative electroencephalography (EEG) test. The efficacy was assessed based on the revised coma recovery scale (CRS-R). Results The results showed a significant increase in CRS-R scores after treatment (Z = −3.668, p < 0.001) without significant adverse effects. Univariate analysis showed that the minimally conscious state minus (MCS–) benefits most from treatment. Furthermore, two frequency have a difference in the time-point of the CRS-R score increase. 5 Hz mainly showed a significant increase in CRS-R score at 2 weeks of treatment (p = 0.027), and 70 Hz additionally showed a delayed effect of a continued significant increase at 1 week after treatment (p = 0.004). Conclusion st-SCS was safe and effective in improving patients with pDOC levels of consciousness, and was most effective for MCS–. Both 5 Hz and 70 Hz st-SCS can promote consciousness recovery, with 70 Hz showing a delayed effect in particular.